Ragam Bentuk dan Desain Sarana Penjahit Keliling di Wilayah Perumahan Bintaro Jaya Sektor 1 dan 2, Jakarta Selatan - Awang Eka Novia Rizali (Institut Seni Indonesia Yogyakarta, 2016)
The national economic changes have effect the life of urban communities. The difficulties of meeting the needs of daily living drive a person tofind a way to increase their income. Mobile tailor is a service to make and to repair the clothes, known also as